Urgensi Pengaturan Pengawasan dan Penegakan Hukum Oleh BPOM Terhadap Tindak Peredaran Obat dan Makanan Ilegal: Basic Urgency of Indonesian FDA (BPOM) Law In Conducting Supervision and Law Enforcement In The field of Drug and Food - Kurniasanti; Joko Setiyono (Law Department, University of Widya Gama Mahakam Samarinda, 2020)
Food and drug arrangement is scattered in several statutory regulations. As the community grows both nationally and internationally, the problems relating to the production, circulation and use of medicinal and food commodities continue to evolve. The country is obliged to safeguard and protect the people of Indonesia, one of which is guaranteed availability of medicines and food that is safe, quality and has benefits. Research Method: This research is a normative, prescriptive study. The research approach includes a regulatory approach of Act No. 36 year 2009 on health and conceptual. Findings: The results of the analysis of the philosophical, sociological and juridical aspects show that to tackle the illegal food and drug distribution needed by BPOM. Conclusion: Based on this, it is important to do the renewal of supervision and law enforcement arrangements on the distribution of drug and illegal food by BPOM through the revision or establishment of statutory regulations.